2019
DOI: 10.1016/j.tem.2019.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin-Mediated Hippocampal Neurogenesis: Implications for Health and Disease

Abstract: Acyl-ghrelin (AG): A Form of ghrelin that has been acylated by GOAT, which enables it to bind to GHS-R1a. Acyl-protein thioesterase 1 (APT1): An endogenous enzyme known to de-acylate acylghrelin Allosteric mechanism: Regulation of a protein or receptor independent of its active site. Brain derived neurotrophic factor (BDNF): A growth factor in the brain, involved in cell proliferation, survival, learning and memory. Bromodeoxyuridine (BrdU): A synthetic thymidine analogue, incorporated into DNA during replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 118 publications
1
31
0
Order By: Relevance
“…49 We therefore propose that acyl-ghrelin promotes hippocampal neurogenesis in a non-cell-autonomous manner. 22,50 To validate this, we show that acyl-ghrelin treatment of hippocampal NSPCs in vitro had no effect on cell proliferation-a result that was consistent with the absence of detectable GHS-R expression in these cells (Figure S7). To determine whether acyl-ghrelin and UAG directly affect the hippocampus, we treated primary hippocampal cultures, which contain a mixed population of cells, including neurons and NSPCs (Figure S6).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…49 We therefore propose that acyl-ghrelin promotes hippocampal neurogenesis in a non-cell-autonomous manner. 22,50 To validate this, we show that acyl-ghrelin treatment of hippocampal NSPCs in vitro had no effect on cell proliferation-a result that was consistent with the absence of detectable GHS-R expression in these cells (Figure S7). To determine whether acyl-ghrelin and UAG directly affect the hippocampus, we treated primary hippocampal cultures, which contain a mixed population of cells, including neurons and NSPCs (Figure S6).…”
Section: Discussionsupporting
confidence: 59%
“…21 These studies clearly identify acyl-ghrelin as an important pro-neurogenic circulating factor. 22 In order to generate acyl-ghrelin, ghrelin must undergo post-translational acylation by the enzyme ghrelin-O-acyl transferase (GOAT), 23,24 prior to binding and activating GHS-R signaling. 25 Unacylatedghrelin (UAG) represents $80%-90% of circulating ghrelin and is often considered an inactive precursor to acyl-ghrelin.…”
Section: Introductionmentioning
confidence: 99%
“…High levels of ghrelin influence the hypothalamus, thereby enhancing individual appetite. At the same time, ghrelin can also regulate the endocrine function and prevent depression after acting on the central nervous system (48,49). Recent studies have shown that ghrelin can regulate glucose and lipid metabolism by inhibiting insulin level in vivo (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been postulated that GHS-R1α is, in fact, not present on immature neuroblasts and that AG possibly drives neurogenesis by stimulating the release of neurogenic factors by GHS-R1α-expressing adult dentate granule cells (Buntwal et al, 2019). Additional studies are needed to confirm these propositions in the hippocampus of healthy rodents and in vivo models of AD, however.…”
Section: Acylated Ghrelin Induces Neurogenesis In the Hippocampusmentioning
confidence: 98%